Four acts dedicated to urban emptiness. An account of a debate on the Seductive Townscape (Bulletin KNOB, 1991)
Quarters considered for large-scaled re-arrangement demand reflection on the discipline of town-planning. The business agreement to realize urban renewal threatens the architect's and town planner's spatial quality and tends to isolation of the renewed area within the extant town. The Dutch Institute of Architecture arranged an exhibition and a debate on the theme of the 'Seductive Townscape'.The culture of urban expansion has changed into a culture of urban transformation. A new interest, mostly proceeding from economic considerations, has arisen in the historical nucleus of the strongly fragmented town of to-day. One of the main purposes in the governmental Fourth Note on Area Planning is improvement of the urban environment to trade and industry.New development strategies as city management and city marketing present themselves by means of the 'seductive townscape'. This approach founds urban renewal on the town's cultural and economical potency. Rivalry between towns has started internationally, which rivalry threatens the urban identity. Top locations to business became 'exchangeable'.Confining measures, which must guarantee the urban identity, decrease the town's chances in the internationally set up contest between towns. Seductive townscapes are developed for the so-called urban emptiness’s. These projects mostly are isolated incidents in the historically grown town. The debate was based on four approaches to 'planning research' as introduced in the catalogue to the exhibition.The plan as embodiment of city marketing (Amersfoort), the plan as script in a theatrical show-piece (Groningen), the plan as a morphological instrument with respect to the town plan's continuity (Maastricht/Rotterdam) and the plan, which Iets architecture and town-planning coincide (site of Sphinx-Céramique, Maastricht).In Amersfoort the Public Private Partnership misses the link with history. Amersfoort's new identity is an example of sheer verbal town-planning, an artist's impression to seduce trade and industry. In Groningen townscapes function as attractions. The traditional bond with the site declines. The Master plan 2000 makes the Department of Area Planning and project developers cooperate.Attention however shifted to architectural filling up too fast. Architects improvise, but the scenario writer is missing. A town-plan not being on hand in Coenen's plan for the Maastricht site of Sphinx- Céramique historical, urban and architectural forms are point of departure. A general hypothesis on the semantic change of the town is missing.In Rotterdam conceptions are coupled with a renewed interest in morphology. The Parklane-draft for Rotterdam-West guarantees an optimal connection of continuity and renewal of urban identity. A clear framework has been created for later architectural detail. Thus the municipality must plan the urban context, fix marks and junctions and watch over the quality of public spaces.Participants of the Public Private Partnership must be roused to comprise their projects both and public spaces in a total plan. Coherence with other parts of the site is important as well. The discipline of town planning must be reconsidered and, laying-out, be forced to an analysis of the morphological and historical urban structure.